GENOME POLITICS: STRATEGY AND TACTICS - Jonas Rubikas (Problemos)
Genome is the whole genetic information of the cell including nuclear, mitochondrial, plastid and other DNA or RNA elements. However, what is the relation between the human cell genome and the genome of total human organism, human personality? Is the genome absolute constant or does the genome change during life, development and evolution of the organism? What is strategy of the genome, and what are the changes, the tactics of the genome seeking to achieve the strategic aim? Is there any difference between human genome and genome for human? Genome controls directly or indirectly all human functions: body structure, physiology. Human mental and consciousness activity, brain functions obtained by learning mask the dependence of these activities on the genome. Even belief in various forms of trascendental phenomena, reincarnation, astral energy influence, energy materialization and many others completely depends on the believer’s genome. Evidence of that is the damage to mental functions in various disorders of genome. The strategy of the genome is multiplication. This is clearly seen when the comparison between the information content (the gene number) and the life cycle of small genomes (plasmids, viruses, singlecellular prokaryotic organisms) is made: large space is occupied by information on replication enzymes and the sequence of replication origin. In higher eukaryotic multicellular organisms the increased complexity of the genome could be expressed as plus function information: for metabolism, for relations with environment, for nervous system. The information can be grouped into special large and smaller programs: for growth, for multiplication, for differentiation and for apoptosis. All these functions again are directed at organism multiplication. In higher multicellular organisms the whole organism genome is stored in special cells - gamets. This genome could be called a strategic genome used only for beginning of a new organism. Every cell of organism has the same genome, but active are only particular program genes, specific for the cell destination; this is a tactic genome. The way of genetic information expression is: DNA-RNA-protein. The accuracy of these three-step processes is under the end-product selection control. For better realization of information in some cases the genome changes the usual way of expression, that is, the genome uses some tactical approaches: at the DNA level - restructuring of the genome (mating type in yeasts, sex determination in some flies and worms, V(D)J recombination in immunoglobulin genes in human B lymphocytes); at the RNA level - gene splicing, alternative and self splicing, RNA editing; at the protein level - protein splicing. Human beings as all living Nature obey the bible trinity law: we are not only parents but also offsprins at the same time, we are joined to each other by the eternal renovation power - the GENOME.